2011
DOI: 10.5539/mas.v5n1p200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Treatments on Seed Germination of Honey Locust (Gleditschia triacanthos)

Abstract: Honey-locust (Gleditschia triacanthos) seeds, like those of many leguminous species, have hard and impermeable coats. Germination is thought to be enhanced when seeds are scarified or soaked in concentrated sulfuric acid or hot water. This experiment was separated into two parts: Scarification methods and stratification investigation. The result from the first experiment showed that acid scarification treatment for 1 hour was the best method for breaking their dormant period. However in the second experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In this regard, Merou et al (2011) also found that the seed coat of Albizia julibrissin became permeable when seeds were immersed in sulfuric acid for 2 hours, which increased germination from 33% to 99%. Our results are consistent with those obtained in other studies of Fabaceae species in which acid scarification made the seed coat water-permeable, thus allowing seeds to imbibe and germination (Orozco-Almanza et al, 2003;Hu et al, 2009;Babashpour et al, 2011;Merou et al, 2011). The results of research on seeds of Acacia auriculiformis (Olatunji et al, 2012) revealed that scarification with concentrated sulfuric acid for 5 and 10 minutes brought about the highest germination percentages (more than 92%) compared to that of the control (42%).…”
Section: Effect Of Different Dormancy Breaking Treatments On Germinatsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, Merou et al (2011) also found that the seed coat of Albizia julibrissin became permeable when seeds were immersed in sulfuric acid for 2 hours, which increased germination from 33% to 99%. Our results are consistent with those obtained in other studies of Fabaceae species in which acid scarification made the seed coat water-permeable, thus allowing seeds to imbibe and germination (Orozco-Almanza et al, 2003;Hu et al, 2009;Babashpour et al, 2011;Merou et al, 2011). The results of research on seeds of Acacia auriculiformis (Olatunji et al, 2012) revealed that scarification with concentrated sulfuric acid for 5 and 10 minutes brought about the highest germination percentages (more than 92%) compared to that of the control (42%).…”
Section: Effect Of Different Dormancy Breaking Treatments On Germinatsupporting
confidence: 91%
“…Most temperate-zone legume species have a water-impermeable seed coat (Hu et al, 2009) that results in physical dormancy (PY); therefore, special pre-treatments are required to promote germination. That is, seed germination percentages may be low, irregular, and prolonged unless a treatment is given to make the seed coat water-permeable (Miyase et al, 2010;Babashpour et al, 2011;Soltani et al, 2016). Under natural conditions, this impermeability may decrease gradually, so that a certain percentage of seeds germinates in each germination season.…”
Section: Introductionmentioning
confidence: 99%
“…Scarified seeds of Albizia lebbeck (L.) by HCl acid, and increasing immersion time to 45min significantly increased germination percentage to 46.67%. This increasing of germination rate also has been reported by other researchers (Abubakar and Maimuna, 2013;Babashpour and Sharifivash, 2010;Noorafkan and Khoshkhui, 2005;Gizachew and Scarisbrick, 1999). The effect of concentrated HCl on stimulation of seed germination might be due to that the acid may soften hard seed coats and allowing easier water uptake and oxygen diffusion resulting in enzymatic hydrolysis and hence transforming the embryo into a seedling (Olatunji et al, 2012;Alamgir and Hossain, 2005).…”
Section: -Germination Parameterssupporting
confidence: 88%
“…Treatment with conc. acid was effective in breaking the seed coat and acid scarification is known to be highly effective in improving germination of species with hard seed coats [4,35]. Some researchers that have been done on Caspian locust, Honey locust [28] and other species of leguminous like as Albizia julibrissin [19] emphasis the effect of sulphuric acid.…”
Section: Figure 3 Germination Of Acid Treated Seeds In Petri Platementioning
confidence: 99%